Can Creative Writing, as an Add-on to Treatment for Alcohol Use Disorder, Support Rehabilitation?. Issue 2 (2nd April 2020) - Tarp, Kristine; Hellum, Rikke; Rasmussen, Anders Juhl; Nielsen, Anette Søgaard
ABSTRACT: Creative writing may help patients find new powers in the acts of making art and expanding horizons beyond illness, including addiction. The aim of the present pilot study was to introduce creative writing workshops to alcohol use disorder (AUD) patients and investigate self-perceived rehabilitating impact, improvement in quality of life, and executive functions. The study was conducted in a mixed methods design; primarily semi-structured group and individual interviews as well as participant observation, supplemented by a small evaluation questionnaire at baseline and follow-up at the end of exposure. The patients had experienced the workshop as having influenced their lives in a positive direction, impacted by doing creative writing, sharing and receiving feedback, and the community of the group. The patients perceived both advantages and disadvantages about discussing alcohol in the workshop. The patients experienced an increase in quality of life from the beginning to the end of the workshop. There could be a need for creative writing workshops as add-ons to ordinary AUD treatment. In such an offer, creative writing might function as a means to improve patient rehabilitation, quality of life, and executive functions.